2017
DOI: 10.1039/c7nr06354g
|View full text |Cite
|
Sign up to set email alerts
|

Multiple polarization states in symmetric ferroelectric heterostructures for multi-bit non-volatile memories

Abstract: Here we report a ferroelectric capacitor structure obtained by alternating ferroelectric and insulator thin-film layers which allows an increase of up to 2 polarization states, with n the number of ferroelectric layers. Four and up to eight distinct, stable and independently addressed polarization states are experimentally demonstrated in this work. The experimental findings are supported by a theoretical model based on the Landau-Ginzburg-Devonshire theory. The key parameter is the change in the strain condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In a Hebbian view [894] , synaptic efficacy arises from a presynaptic cell's repeated and persistent stimulation of a postsynaptic cell. This pre-conditioning is a well-known behavior of any ferroelectric [895] together with their stochastic multi-step polarization switching [896] , [897] , [898] . Oxide spin and multiferroic systems are leading candidates for achieving attojoule-class logic gates for computing containing intrinsic stochasticity and complexity [899] , [900] where spike-timing-dependent plasticity can be harnessed from inhomogeneous polarization switching [901] , [902] , [903] , [904] .…”
Section: Neural Codesmentioning
confidence: 99%
“…In a Hebbian view [894] , synaptic efficacy arises from a presynaptic cell's repeated and persistent stimulation of a postsynaptic cell. This pre-conditioning is a well-known behavior of any ferroelectric [895] together with their stochastic multi-step polarization switching [896] , [897] , [898] . Oxide spin and multiferroic systems are leading candidates for achieving attojoule-class logic gates for computing containing intrinsic stochasticity and complexity [899] , [900] where spike-timing-dependent plasticity can be harnessed from inhomogeneous polarization switching [901] , [902] , [903] , [904] .…”
Section: Neural Codesmentioning
confidence: 99%
“…Other approaches to generate multi-state polarization have focused on the design and control of the architecture of the ferroelectric. For instance, prior work has demonstrated that it is possible to create multi-stability in ferroelectrics by controlling the number of switched ferroelectric layers in multi-layer heterostructures 20,21 or by controlling sequential-polarization switching in films with multiple coexisting structural instabilities 2225 . These efforts, which rely on a single switching pathway between possible structural variants, usually lead to a limited number of switching states that are dictated by the number of film layers or available structural variants.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite‐type oxides are a very important family of materials with the general formula ABO 3 . They exhibit a wide range of ferroelectric, piezoelectric, magnetic, photovoltaic, and photocatalytic properties, which make them widely used in numerous technological applications such as storage memories (ferroelectric random access memories), energy conversion (such as electrolytes in proton‐conducting solid oxide fuel cells and perovskite ferroelectric photovoltaic solar cells), energy harvesters (piezoelectric energy harvesters), and photocatalysis (eg, perovskite SrTiO 3 , KTaO 3 , NaTaO 3 , KNbO 3 , NaNbO 3 , and other perovskite‐type Ti‐containing oxides) …”
Section: Introductionmentioning
confidence: 99%